2015
DOI: 10.1007/s12013-015-0666-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of PSD-93 Deficiency on the Expression of Early Inflammatory Cytokines Induced by Ischemic Brain Injury

Abstract: The aim of the study was to explore the effect of PSD-93 deficiency on the expression of early inflammatory cytokines induced by cerebral ischemia/reperfusion injury. Ten-to twelve-week-old male PSD-93 knockout (PSD-93 KO) mice (C57BL/6 genetic background) and wild-type (WT) littermates were randomly divided into sham and ischemia/reperfusion (I/R) group. The focal cerebral I/R model was established by middle cerebral artery occlusion (MCAO) suture method. RT-PCR was used to detect the mRNA expression of IL-6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…PSD-93 is a scaffold protein in the postsynaptic membrane that mediates the release of inflammatory factors in the early stage of cerebral ischemia through NMDA receptors [16] . In addition, PSD-93 can interact with other proteins with its function structure domain and change the structure and function of other proteins [25][26] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PSD-93 is a scaffold protein in the postsynaptic membrane that mediates the release of inflammatory factors in the early stage of cerebral ischemia through NMDA receptors [16] . In addition, PSD-93 can interact with other proteins with its function structure domain and change the structure and function of other proteins [25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Christopherson et al [27] showed that PSD-95, NMDAR and nNOS can assemble into a macromolecular signal complex, and disrupting ischemia-induced interaction of nNOS with PSD-95 improved regenerative repair after stroke [28][29][30] . In addition, PSD-93 can bind to NR2A and nNOS and facilitate ischemic brain injury [16,31] . On the other hand, neuronal excitatory toxicity interacted with microglia-induced inflammatory response in ischemic brain injury [32][33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSD-93 is a scaffold protein in the postsynaptic membrane that mediates the release of in ammatory factors in the early stage of cerebral ischemia through NMDA receptors [16] . In addition, PSD-93 can interact with other proteins with its function structure domain and change the structure and function of other proteins [25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…PSD-93 binds directly to the carboxyl terminus of N-methyl-D-aspartate (NMDA) receptor subunits NR2A and NR2B via the PDZ domain and transports it to the postsynaptic membrane as a major regulator of synaptic maturation [15] . Our recent study showed that the loss of PSD-93 inhibited pro-in ammatory factors and promoted the expression of antiin ammatory factors, while the application of NMDA receptor (NMDAR) inhibitors provided brain protection [16] . These results suggest that PSD-93 promotes a series of responses to cerebral ischemiareperfusion injury through the activation of NMDAR, including the regulation of in ammatory factor release in early ischemic cells.…”
Section: Introductionmentioning
confidence: 99%